ACUPUNCTURE AND JIANGHUANG HERBS TREATMENT IN ACNE WITH DAMNESS SYNDROME - Agesti, Dyah; Astuti, Suryani Dyah; Mustika, Arifa (Journal of Vocational Health Studies, 2020)
Background : Acne vulgaris is a chronic skin disease that occurs due to chronic inflammation of the pilosebaceous glands. Acne is clinically affected by an increase in sebum, Propionibacterium bacteria acne, hormones, genetic, stress, diet and the environment. In Chinese Medicine, acne vulgaris belongs to categories of Feng Ci, it is caused by wind-heat pathogens that attack the lungs and excessive consumption of spicy and oily foods resulting in accumulation of heat in the stomach and intestines. In Chinese Medicine, sebaceous glands are associated with the Lung and Spleen. Patients classified as acne with differentiation of accumulation of phlegm syndrome. Purpose: To know the effect of acupuncture therapy at LI-4 Hegu, ST-36 Zusanli , ST-40 Fenglong, SP-6 Sanyinjiao and herbal therapy using Jianghuang in patients Acne vulgaris with differentiation of accumulation of phlegm syndrome. Method: Acupuncture therapy at LI-4 Hegu, ST-36 Zusanli , ST-40 Fenglong, SP-6 Sanyinjiao were given 12 times, 3 times a week, with the principle of therapy to reinforce phlegm, strengthen the spleen and raise the spleen. In herbal therapy the patient is given herbal Jianghuang (Curcuma longa.L) dose of 3 grams 12 times, 3 times a week. Result: Compound of curcumin which is antibacterial, anti-inflammatory, antioxidant and wound healing affects acne. Acupuncture and herbal therapy given 12 times, 3 times a week can overcome acne vulgaris. Conclusion: Acupuncture and herbal therapy can overcome the growth of acne.